Evaluation of bioactive components and proliferation properties of different royal jelly samples: Study about different royal jelly samples. - Özkök, Asli; Akbay, Esin; Tanuğur Samancı, Aslı Elif; Mayda, Nazlı; Onur, Mehmet Ali (Progress in Nutrition, 2021)
In this study cell proliferation potentials were evaluated of different royal jelly. Physical, chemical and palynological analysis were done at the royal jelly samples, which are collected 5 different regions (RJ1: Balıkesir 1, RJ2: Bursa 1, RJ3: Çanakkale 1, RJ4: Yalova 1, RJ5: Bursa 2) of Turkey. In addition to this, cell proliferation potentials of these different royal jelly samples were evaluated by 3-(4,5-dimethylthiazoyl-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay. All analysis results were found to vary from region to region. MTT results indicated that after 24h incubation, RJ2 and RJ4 dilutions significantly different from control. However, light microscopy analysis showed same groups caused less viability potential in adipose derived mesencymal stem cells after 72h incubation. On the other hand, the highest dilutions of RJ1 and RJ3 cause more cell death with IC50 potential after 72h incubation. Among all groups, the lowest concentration of RJ5 has been shown to have the best growth-stimulating activity on adipose derived mesenchymal stem cells. The results of cell viability test highlight the potential differences of royal jelly samples on stem cell growth stimulation.